Prediksi Perubahan Penggunaan Lahan Tahun 2034 Dengan Permodelan Cellular Automata Di Kabupaten Semarang - Zahrayni, Alfayra Nabila; Tjaturahono Budi Sanjoto; Rahma Hayati; Ariyani Indrayati (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2025)
Land use changes reflect the dynamic growth of a region driven by continuously evolving human activities. Semarang Regency, located in Central Java Province, is currently experiencing significant land use changes due to suburbanization, population growth, and increasing population density each year. This study aims to predict land use changes in Semarang Regency as a basis for identifying potential non-compliance with the RTRW, referring to the renewal of the RTRW before the end of its validity period.To analyze these changes, a spatial approach using Geographic Information System (GIS) and Remote Sensing is essential to map land use in 2013, 2018, and 2024. This analysis is further integrated with Cellular Automata (CA) modelling and logistic regression to identify factors influencing land use changes and to predict land use patterns in Semarang Regency through 2034. The study predicts that by 2034, built-up land will expand by 9.315,83 hectares, while agricultural land will increase by 9.054,79 hectares. Conversely, forest and conservation land are projected to decrease by 18.433 hectares, and water bodies will shrink by approximately by 53,94 hectares. The results of this prediction can be used as a reference in preparing spatial planning policies that are more adaptive and in line with field conditions.